Effect of A Deltamethrin Incorporated Polypropylene Storage Bags on Germination Percentage of Dressed Maize Seed Under Storage in Trans Nzoia County, Kenya - Tegei, Eric Maghas; Githendu, Mukiri; Muui, Catherine W. (European Journal of Applied Sciences, 2023)
Seed storage structures have a great influence on the quality of the stored seed. The level of insect-pest infestation, damages or losses, and overall quality of the stored seed over some time depends on the kind of storage structure used. The purpose of this study was to determine the effectiveness of a Deltamethrin-incorporated polypropylene storage bag against the insect pest infestation on dressed maize seeds quality in Kitale, Trans Nzoia County, Kenya. The target population was all the insect-free maize Seed at Kenya Seed Company Ltd, Elgon Downs Farm located on the outskirts of Kitale Town. The study was operationalized with a Complete Randomized Research Design with four treatments and two replications each. Data was collected by using pre-prepared data sheets while the Excel package was used for data management and the stratigraphic software was used to analyze the insect damage-related data. T-test was also used to establish the direction of effect between the various sample results. The analyzed data was presented in graphs and tables. The study concluded that Deltamethrin-incorporated polypropylene bags had better efficacy in providing deterrence on insect infestation, hence, a better storage material compared to the control bags. From these conclusions, the study recommends that the ministry through extension services should educate large-scale farmers on the use of the Deltamethrin-incorporated polypropylene bags. The county officials in charge of agricultural services can also educate small-scale farmers on the use of these bags and collaborations between the national and county governments could be harnessed to ensure their availability at affordable rates to farmers.